Land Cover Change Detection Using Landsat Data in Giao Thuy District, Nam Dinh Province, Vietnam - Lan, Nguyen Tuyet; Osawa, Takahiro; Nuarsa, I Wayan; An, Ngo The (International Journal of Environment and Geosciences; Vol 1 No 1 (2017)DO - 10.24843/ijeg.2017.v01.i01.p03, 2017)
Giao Thuy located a coastal area, which has fully the characteristed of microclimate Red River delta. This study was conducted to detect the land cover changes from 2000 to 2015 and the causes. The changes are evaluated using Landsat data by method of land use classification combined with interviews. The results showed that most portion of the land cover class was crops land and land cover change was crops land decreases, forest land rises, aquaculture ponds increase, surface water reduces and unuse flat land area increases. The causes were policy issuses, market, economic, salinity intrusion, climate change and deposits alluvial.
Keywords: land cover change, landsat data, the cause of driving force